If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21x + 7 = 10x + -1 Reorder the terms: 7 + 21x = 10x + -1 Reorder the terms: 7 + 21x = -1 + 10x Solving 7 + 21x = -1 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 7 + 21x + -10x = -1 + 10x + -10x Combine like terms: 21x + -10x = 11x 7 + 11x = -1 + 10x + -10x Combine like terms: 10x + -10x = 0 7 + 11x = -1 + 0 7 + 11x = -1 Add '-7' to each side of the equation. 7 + -7 + 11x = -1 + -7 Combine like terms: 7 + -7 = 0 0 + 11x = -1 + -7 11x = -1 + -7 Combine like terms: -1 + -7 = -8 11x = -8 Divide each side by '11'. x = -0.7272727273 Simplifying x = -0.7272727273
| 5(g-6)=48 | | 1.5x=1.23 | | r-9-(-42)=96 | | 9+4+10=56 | | 8(3x+40)=10 | | x^2-320=x-10 | | 3overx= | | 15=k-32 | | 3x+2-2=8-2 | | 18p-15=0 | | T(-3)=21 | | 2X+1=-x+2 | | -x+(-x)+(-x)+(-z)= | | 1.6k=5.75 | | 2x+12=3x-9 | | (x^2)+30x-2000=0 | | n-11=66 | | 11y+5=3(-5+2y) | | -.9x^2+45x=0 | | 8x-12-6x-1=1 | | v-52=29 | | 2(6x-10)=31-3(5-3x) | | -24x+-6+7x+9x-27=4 | | p-6=43 | | h*7=15 | | -3x^2+36x-33=0 | | a^2-10+9a=0 | | 9(2x-3)=27 | | 6x+29=-4x-1 | | 7x=9+-3(x+1) | | 3y+y=-40 | | -3(1-n)=6-6n |